2003
DOI: 10.1039/b210500b
|View full text |Cite
|
Sign up to set email alerts
|

Metastable forms of the tetragonal phase in compositionally homogeneous, nanocrystalline zirconia–ceria powders synthesised by gel-combustion

Abstract: International audienceThe crystal structure of compositionally homogeneous, nanocrystalline ZrO2–10, 30, 50, 70 and 90 mol% CeO2 powders synthesised by a pH-controlled nitrate–glycine gel-combustion process has been studied by X-ray diffraction and Raman spectroscopy. All the powders with a CeO2 content up to 70 mol% exhibited the tetragonal phase (P42/nmc space group), whereas the ZrO2–90 mol% CeO2 solid solution presented the cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 24 publications
0
52
0
3
Order By: Relevance
“…However, this splitting is not evident in nanosized Zr 0.5 Ce 0.5 O 2 powders, because of the very small particle size and the resulting broad XRD peaks. Nevertheless, a marked asymmetry indicative of such splitting is observed in this peak [11][12][13].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, this splitting is not evident in nanosized Zr 0.5 Ce 0.5 O 2 powders, because of the very small particle size and the resulting broad XRD peaks. Nevertheless, a marked asymmetry indicative of such splitting is observed in this peak [11][12][13].…”
Section: Resultsmentioning
confidence: 90%
“…Several routes have previously been used for the synthesis of compositionally homogeneous nanocrystalline ceria-based solid solutions, including the sol-gel method [7], hydrothermal synthesis [8], the polymerized complex method [9], the amorphous citrate process [10] and gel-combustion [11]. Lamas et al [12] reported a study of the tetragonal-cubic phase transition on nanocrystalline powders obtained by a pH-controlled nitrateglycine gel-combustion method (average crystallite sizes were in the range of 8-20 nm).…”
Section: Introductionmentioning
confidence: 99%
“…a reduction of the peak intensity, especially at low angles. Bfactors (isotropic temperature factor) were fixed for each element to standard values, without modifying the quality of the fit [25,26].…”
Section: Structural and Microstructural Analysesmentioning
confidence: 99%
“…The production process of ZrO 2 -Al 2 O 3 (ZrO 2 -AlO(OH)) nanopowders follows various chemical routes, such as sol-gel method [4,[18][19][20], hydrothermal synthesis [21,22] or co-precipitation method [23,24]. It was found [25] that the main benefit of hydrothermal synthesis is the generation of weakly agglomerated nanopowder.…”
Section: Introductionmentioning
confidence: 99%